Strength Analysis of a Two-Layer PETF-Concrete Column with Allowance for Contact Interaction between Layers. (23rd September 2021) - Velychkovych, Andrii; Ropyak, Liubomyr; Dubei, Olga
Abstract : This article develops an idea of mechanical recycling of polymer wastes. Unlike previous research studies, which are dedicated to the study of the physical and mechanical properties of fibrous concrete and the technology of its manufacturing, this work considers a specific construction product—laminated concrete column made of recycled polyethylene terephthalate (PETF). Currently, there are no policy documents (standards or codes) regarding the engineering design of such constructions. Therefore, the authors' attention is focused on mechanical and mathematical modeling of the laminated column behavior under operational load. An analytical study of two-layer PETF-concrete column's stress-strain state was performed, taking into account the contact interaction between inhomogeneous layers of the materials. It has been determined that, in certain circumstances, the contact pressure between the layers can have a significant effect on the load-bearing capacity of the column. In general, a method of engineering assessment of laminated columns' load-bearing capacity was developed.